The Impact of Cervical Musculoskeletal Disorders on UK Consultant Plastic Surgeons: Can We Reduce Morbidity With Applied Ergonomics?. Issue 6 (June 2017) - Godwin, Yvette; Macdonald, Christopher R.; Kaur, Sarbjit; Zhelin, Li; Baber, Christopher
Abstract : Background: Based on anecdotal and observational evidence, we hypothesized that the prevalence of cervical musculoskeletal disorder (C-MSD) would be high among plastic surgeons. A questionnaire review was undertaken to test this hypothesis. Ergonomic assessment was undertaken to assess causal factors of C-MSD. Method: An anonymous questionnaire recording demographics, physical symptoms and behavioral responses to C-MSD was distributed to UK Plastic Surgery consultants. The postural impact of wearing loupes was assessed using motion capture techniques and recording cervical muscular activity. Results: The questionnaire response rate was 81%. The prevalence of cervical spine morbidity was recorded as 32%. Employment implications included 28% of the cohort requiring sick leave. The professional impact was 7% permanently modifying their practice. There were 2 factors significant for C-MSD, the surgeons' age and the duration in hours of wearing loupes per week. Ergonomic assessment of surgeons operating in loupes demonstrated: 1. increased forward and lateral cervical flexion; 2. increased cervical muscular activity to maintain the protracted "head forward" posture; and 3. prolonged static posturing to maintain head position for visual focus. Table height adjustment and variation of loupe working distance can reduce neck flexion. Conclusions: Cervical morbidity is a prevalent problem among plastic surgeons. Long procedures, static postures and neck flexion result in the "head forward" posture. This posture exaggerates when operating with loupe magnification. Early-middle-aged consultants are more prone to cervical morbidity hence afflicted when at the top of their game. The work force is diminished for a potentially avoidable morbidity. Rather than accept this morbidity, co-operation between plastic surgeons and ergonomist may help to reduce injury. Abstract : Supplemental digital content is available in the text.